2013
DOI: 10.2217/cer.13.54
|View full text |Cite
|
Sign up to set email alerts
|

Compassion as the foundation of patient-centered care: the importance of compassion in action

Abstract: The Institute of Medicine defines patient-centered care as "providing care that is respectful of, and responsive to, individual patient preferences, needs and values, and ensuring that patient values guide all clinical decisions." What is missing in this definition is an explicit emphasis on compassion. This perspective article draws on the experience of Planetree (CT, USA), a not-for-profit organization that partners with healthcare establishments to drive adoption of patient-centered care principles and prac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
64
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(65 citation statements)
references
References 50 publications
0
64
0
1
Order By: Relevance
“…The findings here support the theoretical assumptions that pressure to perform under stressful conditions in unsupportive environments can erode nurses’ compassion (Cole‐King & Gilbert, ), and that more is needed to help them develop self‐care techniques to face these circumstances. Barriers to learning about and displaying compassionate care are well documented in the literature (Frampton, Guastello, & Lepore, ; Guastello & Frampton, ), to the degree where some argue that the move to degree from trained nurses could have been partly responsible for what happened at Mid‐Staffordshire (Francis, ). Nurses there were encouraged to focus on targets more than care (Darbyshire & McKenna, ).…”
Section: Discussionmentioning
confidence: 99%
“…The findings here support the theoretical assumptions that pressure to perform under stressful conditions in unsupportive environments can erode nurses’ compassion (Cole‐King & Gilbert, ), and that more is needed to help them develop self‐care techniques to face these circumstances. Barriers to learning about and displaying compassionate care are well documented in the literature (Frampton, Guastello, & Lepore, ; Guastello & Frampton, ), to the degree where some argue that the move to degree from trained nurses could have been partly responsible for what happened at Mid‐Staffordshire (Francis, ). Nurses there were encouraged to focus on targets more than care (Darbyshire & McKenna, ).…”
Section: Discussionmentioning
confidence: 99%
“…In clinical settings, compassion actuates healthcare providers to provide care that focuses on a patient's humanity and uniqueness [4]. Healthcare encounters that include compassion can offer substantial benefits for patients, such as increasing trust in the patient-physician relationship, improving patient satisfaction, symptoms and quality of life and aiding recovery [1,5,[7][8][9][10][11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…In several studies, patients and their families have identified compassion as a necessity during healthcare encounters [7]. A recent systematic review of compassion in healthcare [5] identified compassion as a patient right [18], central to codes of ethics across healthcare professions [19][20][21], a practice competency that should be evaluated in selecting medical and nursing student admissions, [22,23], a standard of care that healthcare providers must be trained in and systems must measure and report [11,17,24] and a dimension of quality care that should be assessed on an ongoing basis [17,25].…”
Section: Introductionmentioning
confidence: 99%
“…The strength of evidence is such that educational frameworks like CanMEDS [2] (an internationally used set of educational and practice competencies physicians require to effectively meet patient needs) enshrine the value of empathy in multiple roles including communicator, collaborator (where situational awareness is emphasized) and professional, with its focus on altruism, self-care and compassion [2]. Closely aligned with empathy is compassion, “a deep feeling of connectedness with the experience of human suffering that requires personal knowing of the suffering of others, evokes a moral response to the recognized suffering that results in caring that brings comfort to the sufferer” [21], and the ability to relate to the vulnerability of others in a meaningful way [18]. Contemporary medical pedagogy generally includes concepts of professionalization, emotional well-being, and clinical empathy [22].…”
Section: Introductionmentioning
confidence: 99%